2023
DOI: 10.3389/fpubh.2022.1040676
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric and visualization analysis of research trend in mental health problems of children and adolescents during the COVID-19 pandemic

Abstract: ObjectivesTo analyze the evolution of research on children and adolescents mental health issues during COVID-19 pandemic and discuss research hotspots and cutting-edge developments.MethodsThe literature obtained from the web of science core collection as of June 28, 2022, was analyzed using Citespace, VOSviewer bibliometric visualization mapping software.ResultsA total of 6,039 relevant papers were found, of which 5,594 were included in the study. The number of literatures is growing since 2020; and the countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
5
0
1
Order By: Relevance
“…For this reason, call-to-action for longitudinal mental health research during (and after) the COVID-19 pandemic has been raised to understand the long-term impact of the pandemic on children and adolescents [ 7 , 8 ]. Although systematic reviews suggested a deterioration in mental health among children and youths from before to during the pandemic, there was little direct evidence from longitudinal studies [ 9 , 10 ]. The present study thus aimed to investigate the impact of the pandemic on adolescent non-suicidal self-injury (NSSI) and examine psychological risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, call-to-action for longitudinal mental health research during (and after) the COVID-19 pandemic has been raised to understand the long-term impact of the pandemic on children and adolescents [ 7 , 8 ]. Although systematic reviews suggested a deterioration in mental health among children and youths from before to during the pandemic, there was little direct evidence from longitudinal studies [ 9 , 10 ]. The present study thus aimed to investigate the impact of the pandemic on adolescent non-suicidal self-injury (NSSI) and examine psychological risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, based on our previous bibliometric study on cyberbullying, it was found that (a) no bibliometric study had analyzed the literature on the nexus of cyberbullying and mental health and (b) mental health is one of the major fields of study in collaboration with cyberbullying (Bansal et al, 2023a ). Although various authors have used a vast list of keywords while retrieving a dataset on mental health (Guo et al, 2023 ), they have skipped many terms; for instance, “suicidal,” “suicidal tendency,” “suicide,” “suicidal ideation,” and “deviant behavior.” Also, it was observed during our extensive literature review, apart from specifying mental disorder, the term “mental health” was also used as one of the keywords or extended keywords. Therefore, we have used “mental health” as an umbrella term to not to skip any study that might have explored any one mental health problem arising out of cyberbullying.…”
Section: Methodsmentioning
confidence: 99%
“…Según AlRyalat et al (2019), mientras que PubMed se especializa en la investigación biomédica y de ciencias de la vida, tanto WoS como Scopus son preferibles para la investigación multidisciplinar debido a su amplio alcance y cobertura. Por ello, se eligió WoS de Clarivate en lugar de Scopus de Elsevier, ya que WoS se ha elegido comúnmente como fuente de datos para estudios de análisis bibliométrico de salud mental (Berta et al, 2022;Guo et al, 2023;Urbán et al, 2023;Zhu et al, 2023) y deserción universitaria (Gutiérrez-de-Rozas et al, 2022;Véliz Palomino & Ortega, 2023;Wang et al, 2023) en los últimos años. En segundo lugar, WoS ofrece una amplia base de datos que abarca 256 disciplinas, lo que permite realizar búsquedas y análisis de información más precisos que otras bases de datos (Cansun & Arik, 2018).…”
Section: Metodologíaunclassified